Preclinical target validation for non-addictive therapeutics development for pain. (2nd September 2022) - Hargreaves, Richard; Akinsanya, Karen; Ajit, Seena K.; Dhruv, Neel T.; Driscoll, Jamie; Farina, Peter; Gavva, Narender; Gill, Marie; Houghton, Andrea; Iyengar, Smriti; Jones, Carrie; Kavelaars, Annemieke; et al.
ABSTRACT: Introduction: The Helping to End Addiction Long-term SM Initiative supports a wide range of programs to develop new or improved prevention and opioid addiction treatment strategies. An essential component of this effort is to accelerate development of non-opioid pain therapeutics. In all fields of medicine, therapeutics development is an arduous process and late-stage translational efforts such as clinical trials to validate targets are particularly complex and costly. While there are plentiful novel targets for pain treatment, successful clinical validation is rare. It is therefore crucial to develop processes whereby therapeutic targets can be reasonably 'de-risked' prior to substantial late-stage validation efforts. Such rigorous validation of novel therapeutic targets in the preclinical space will give potential private sector partners the confidence to pursue clinical validation of promising therapeutic concepts and compounds. Areas covered: In 2020, the National Institutes of Health (NIH) held the Target Validation for Non-Addictive Therapeutics Development for Pain workshop to gather insights from key opinion leaders in academia, industry, and venture-financing. Expert opinion: The result was a roadmap for pain target validation focusing on three modalities: 1) human evidence; 2) assay development in vitro ; 3) assay development in vivo .